(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
To exhibit the meanings attributed to quality of life by patients with facial melasma. Methods: Qualitative research using the focal group technique, with 10 people with facial melasma from a public hospital and private clinic of a municipality in the interior of the state of São Paulo. The methodological indicative used was content analysis. Results: In the interviewees’ speech, one perceives the annoyance generated by the opinion of others, with curious and even malicious questions related to the blemish. There is difficulty to hide the injuries and the appearance of skin neglect is also cause for distress for the participants. Conclusion: Because it affects the face, which makes it easily visible, melasma is uncomfortable and has a negative impact on the quality of life, since it affects patients’ psychological and emotional well-being.